2021
DOI: 10.3390/cells11010124
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-like Cells Promote Neuronal Functions in Cerebral Organoids

Abstract: Human cerebral organoids, derived from induced pluripotent stem cells, offer a unique in vitro research window to the development of the cerebral cortex. However, a key player in the developing brain, the microglia, do not natively emerge in cerebral organoids. Here we show that erythromyeloid progenitors (EMPs), differentiated from induced pluripotent stem cells, migrate to cerebral organoids, and mature into microglia-like cells and interact with synaptic material. Patch-clamp electrophysiological recordings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 99 publications
4
57
0
Order By: Relevance
“…Erythromyeloid progenitors (EMPs), microglia precursors, were generated from iPSCs and incorporated to cerebral organoids at an early maturation stage (Fagerlund et al, 2021).…”
Section: Increasing Cortical Organoids Cellular Complexity: Potential...mentioning
confidence: 99%
See 4 more Smart Citations
“…Erythromyeloid progenitors (EMPs), microglia precursors, were generated from iPSCs and incorporated to cerebral organoids at an early maturation stage (Fagerlund et al, 2021).…”
Section: Increasing Cortical Organoids Cellular Complexity: Potential...mentioning
confidence: 99%
“…Due to the different germ layer origin, microglial cells are not present in cortical organoids and need to be infiltrated from external sources ( Figure 1 ). Transplantation of primary human fetal microglia or iPSC-derived microglial progenitors ( Fagerlund et al, 2021 ; Popova et al, 2021 ) showed that microglia or their precursors can spontaneously integrate in the organoid tissue, eventually transitioning from an immature amoeboid state to a ramified morphology indicating a homeostatic surveillance role ( Fagerlund et al, 2021 ; Popova et al, 2021 ).…”
Section: Increasing Cortical Organoids Cellular Complexity: Potential...mentioning
confidence: 99%
See 3 more Smart Citations